Design and Evaluation of General Purpose, Barrier, and Multichannel Plasticating Extrusion Screws. Issue 4 (16th January 2020) - Kazmer, David O.; Grosskopf, Clemens M.; Rondeau, David; Venoor, Varun
Abstract : Extrusion screw designs and validation are presented for three multiple channel, fractal screws for comparison with common general purpose, and barrier screws using an instrumented single screw extruder with high impact polystyrene (HIPS) and low density polyethylene (LDPE) at varying screw speeds. The fractal screws are designed with multiple channels and pressure–volume–temperature relations to control shear heating with cooling by adiabatic decompression. The general‐purpose design had the highest throughput but did not provide sufficient mixing and so resulted in excessive variation in the melt temperature and pressure at screw speeds above 40 RPM. The barrier screw was a capable design with good performance for LDPE and HIPS with screw speeds from 20 to 60 RPM. However, it tended to provide excessive shear heating at higher screw speeds due to the large surface area of the barrier and mixing sections. The first fractal screw design was a multichannel variant of the general‐purpose design and exhibited good consistency but excessive heating due to the large bearing area between the flights and barrel. The second fractal screw design provided decompression in the feed zone and metering zone to improve throughput but was limited by a poor transition section design. The third fractal screw design remedied these deficiencies with an improved transition section and intermittent clearances for dispersive mixing. Its performance rivaled that of the barrier screw with respect to volumetric output and energy efficiency but provided better melt pressure consistency. Cold screw freezing experiments were performed for all five screws with 5% black, blue, and violet colorants serially added to neat HIPS. The cold screw pulls showed that the general purpose and barrier screws exhibited significant racing of the materials within their screw channels and, thus, broad residence time distributions. Examination of the material cross sections indicated persistent coiled sheet morphologies, which were best dispersed with the third fractal screw. POLYM. ENG. SCI., 60:752–764, 2020. © 2020 The Authors. Polymer Engineering & Science published by Wiley Periodicals, Inc. on behalf of Society of Plastics Engineers.